2021
DOI: 10.3390/toxics9030050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of 9-OH- and 7,8-diol-benzo[a]pyrene in Blood as Potent Markers of Cognitive Impairment Related to benzo[a]pyrene Exposure: An Animal Model Study

Abstract: The potent neurotoxicity of benzo[a]pyrene (B[a]P) has been suggested to be a susceptibility factor accelerating the onset of brain tumours and the emergence of neurobehavioural disturbances. B[a]P has been shown to be neurotoxic, acting directly on both the central and peripheral nervous systems, as well as indirectly via peripheral organs like liver and gut. By using a realistic B[a]P exposure scenario (0.02–200 mg/kg/day, 10 days) in mice, we elucidated brain-specific B[a]P metabolism and at identified hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…In another study, [ 118 ] B[ a ]P (20 and 200 mg/kg/day) was repeatedly given to mice, causing a significant overexpression of cytochrome. An elevated expression of Cyp1A1 / Cyp1B1 was noted in two of the three brain regions, showing the brain’s capability to metabolize B[ a ]P alone.…”
Section: Metabolism Of B[ a ]Pmentioning
confidence: 99%
“…In another study, [ 118 ] B[ a ]P (20 and 200 mg/kg/day) was repeatedly given to mice, causing a significant overexpression of cytochrome. An elevated expression of Cyp1A1 / Cyp1B1 was noted in two of the three brain regions, showing the brain’s capability to metabolize B[ a ]P alone.…”
Section: Metabolism Of B[ a ]Pmentioning
confidence: 99%
“…The brain is one of the extrahepatic tissues that express CYP1A1 both constitutively and following induction [ 30 , 31 ]. In a recent study, exposure to B[a]P by oral gavage at 20 and 200 mg/kg for 11 consecutive days induced significant overexpression of Cyp1a1/Cyp1b1 in the frontal cortex, temporal cortex, and hippocampus regions of mouse brains [ 32 ]. The difference in the result of Cyp1b1 between the previous study and the present study might be due to the difference in exposure level.…”
Section: Discussionmentioning
confidence: 99%
“…After oral administration of benz­[ a ]­anthracene (BaA), the concentration of BaA in organs of Fisher-344 rats was in the order of kidney > spleen > liver > lung > muscle > heart from high to low . Cherif et al reported that after oral exposure to B­[a]P in Balb/c mice, rich B­[a]­P were detected in the brain . This shows that after oral administration of PAHs, they can accumulate in a variety of organs by entering the bloodstream.…”
Section: Tissue Distribution Of Pahs and The Derivatives In Vivomentioning
confidence: 99%